Англомовна підготовка майбутніх вертольотчиків до ведення радіообміну - Зеленська, О. М.; Zelenska, O. M.; Марченко, О. Г.; Marchenko, O. H.; Онипченко, П. М.; Onypchenko, P. M.; Кондра, О. В.; Kondra, O. V.; Ольга Марченко (Науковий вісник Льотної академії. Серія : Педагогічні науки. - 2021. - Вип. 10. - С. 160-168, 2021)
Навчання авіаційної англійської є специфічним за цілями, змістом, критеріями володіння, відповідними професійними й особистими показниками та умовами використання. Дана підготовка повинна відбуватись з поступовим нарощуванням складності завдань, просуванням курсантів від заучування та відтворення мовних структур до самостійного моделювання ситуацій професійного спілкування. Водночас проведене дослідження свідчить, що недоцільно в навчанні курсантів орієнтуватися лише на стандартну фразеологію радіообміну. Тому, у випадках, коли стандартна фразеологія не «пропонує жодних типових форм словесної комунікації» вертольотчикам пропонується переходити на звичайну англійську мову, що актуалізує проблему збагачення англомовного арсеналу авіаційних фахівців.

The complex nature of the professional activities of helicopter pilots actualizes a systematic approach to determining their readiness to perform their duties when flying in international airspace. At the same time, participation in peacekeeping operations, rescue expeditions, evacuation of the population makes increased demands on the level of their foreign language training in the higher military educational institution of aviation profile. Aviation English training is specific in terms of purpose, content, proficiency criteria and relevant professional and personal indicators and conditions of use. Given the importance of radio exchange in ensuring trouble-free flight activities, the article analyses the process of Englishlanguage preparation of future helicopter pilots for radio exchange at the main stages of the training flight. This training should take place with a gradual increase in the complexity of tasks, the advancement of cadets from learning and reproduction of language structures to independent modelling of professional communication situations. It involves the involvement of such resources of the information and educational environment of higher education institutions as regular classrooms with classrooms and / or interactive whiteboards, language classrooms, training cabins of Mi-2, Mi-8, Mi-24 helicopters, located in specialized classrooms. The most successful place to practice radio communication skills is an aviation simulator, which allows you to practice not only the speech response, but also the motor response to control the helicopter. Intelligence computer simulations of helicopter motion are promising, which creates unique opportunities for creating radio exchange learning situations. At the same time, the study of this issue allowed us to conclude that it is inexpedient in teaching cadets to focus only on standard phraseology of radio exchange, as the latter, although it helps to avoid misunderstandings, is not able to describe all possible circumstances and reactions. Therefore, in cases where the standard phraseology does not "offer any typical forms of verbal communication, pilots and air traffic controllers switch to ordinary English", which raises the issue of enriching the English-speaking arsenal of aviation professionals.

Исследовано усовершенствование англоязычной подготовки будущих вертолетчиков к ведению радиообмена в условиях высшего военного учебного заведения авиационного профиля. Проведенное исследование свидетельствует, что нецелесообразно в обучении курсантов ориентироваться только на стандартную фразеологию радиообмена. Поэтому, в случаях, когда стандартная фразеология не «предлагает никаких типичных форм словесной коммуникации» вертолетчикам предлагается переходить на обычный английский язык, что актуализирует проблему обогащения англоязычного арсенала авиационных специалистов.
English training of future helicopters to radio exchange
Keywords: вищий військовий навчальний заклад авіаційного профілю; higher military educational institution of the aviation profile; высшее военное учебное заведение авиационного профиля; професійна підготовка; professional training; профессиональная подготовка; англомовна підготовка; English training; англоязычная подготовка; вертольотчик; helicopter pilot; вертолетчик; радіообмін; radio exchange; радиообмен; фразеологія; phraseology; фразеология